2011
DOI: 10.1007/s13311-011-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cell-Based Therapies and Neural Prostheses to Promote Neural Survival

Abstract: Cochlear implants provide partial restoration of hearing for profoundly deaf patients by electrically stimulating spiral ganglion neurons (SGNs); however, these neurons gradually degenerate following the onset of deafness. Although the exogenous application of neurotrophins (NTs) can prevent SGN loss, current techniques to administer NTs for long periods of time have limited clinical applicability. We have used encapsulated choroid plexus cells (NTCells; Living Cell Technologies, Auckland, New Zealand) to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 57 publications
4
79
0
Order By: Relevance
“…However, the use of osmotic pumps to deliver neurotrophic factors clearly is not a good option for clinical application, particularly due to concerns about infection Staecker et al 2010). Numerous recent studies have explored alternative strategies for cochlear delivery of neurotrophins (Hendricks et al 2008;Richardson et al 2008), including cell-based therapies (Warnecke et al 2007;Pettingill et al 2008;Wise et al 2011), hydrogels (Endo et al 2005, and gene therapy using adenovirus-mediated expression of neurotrophic factors (Nakaizumi et al 2004;Rejali et al 2007;Chikar et al 2008;Wise et al 2010). These methods may provide better alternatives in the future, but they are still under development and concerns about potential side effects and risks have not yet been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of osmotic pumps to deliver neurotrophic factors clearly is not a good option for clinical application, particularly due to concerns about infection Staecker et al 2010). Numerous recent studies have explored alternative strategies for cochlear delivery of neurotrophins (Hendricks et al 2008;Richardson et al 2008), including cell-based therapies (Warnecke et al 2007;Pettingill et al 2008;Wise et al 2011), hydrogels (Endo et al 2005, and gene therapy using adenovirus-mediated expression of neurotrophic factors (Nakaizumi et al 2004;Rejali et al 2007;Chikar et al 2008;Wise et al 2010). These methods may provide better alternatives in the future, but they are still under development and concerns about potential side effects and risks have not yet been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the application of neurotrophins into the scala tympani enhances the survival and density of peripheral processes of the SGNs [2], attracts neurites into the scala tympani [3], and even reduces electrically evoked auditory brainstem response thresholds [4]. Cell-based approaches have been suggested for a sustained neurotrophin supply.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based approaches have been suggested for a sustained neurotrophin supply. For example, xenogenic choroid plexus cells [2] and genetically modified fibroblasts [5] have been implanted into the scala tympani. Adipose-derived stem cells (ASCs), multipotent stem cells that can be harvested from adult individuals, are also known to produce neurotrophins [6] and can be used autologously, thereby being more suitable for the application in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although introducing alien cells into the cochlea bears risk of immune response or migration, several techniques have been developed to considerably minimize these risks (Rejali et al, 2007;Pettingill et al, 2011;Wise et al, 2011). Rejali et al (2007) showed that BDNF-releasing fibroblasts attached to a cochlear implant electrode have a positive effect on SGC survival in the basal half of the cochlea after 48 h. However, the life span of these fibroblasts was limited to several weeks, probably due to fixation of the cells to the electrode.…”
Section: Cell-based Therapy For Permanent Neurotrophic Supplymentioning
confidence: 99%